The Meaning of "Dare Demo Nai Otoko" (誰でもない男) within the Perspective of Friedrich Nietzsche’s Philosophy: (Case Study of Obito Uchiha: Naruto Shippuden Chapter 564) - rifqi khairul anam (Dekonstruksi, 2026)
This article presents a philological and phenomenological analysis of the key phrase Dare demo Nai Otoko (誰でもない男) as articulated within the narrative of Naruto Chapter 564. Employing a textual hermeneutic approach, this study dissects the syntactic structure of the phrase to distinguish it from the concept of spatial absence (dare mo inai), illuminating an ontological paradox wherein the presence of bodily facticity (otoko) coexists with the negation of subjective essence (nai). The research primarily focuses on how this linguistic construction facilitates the subject's transition from a historically bound social entity into an anonymous "operational mechanism." This analysis posits that such identity negation is not mere rhetoric of self-defense, but a structural prerequisite for the subject to attain systemic immunity and enact a radical intervention against an order of reality deemed to have lost its epistemological validity. These findings offer a novel theoretical framework for understanding the dynamics of self-dissolution as a strategy of agency within conditions of a meaning crisis.